REVOLUTIONIZING BUSINESS MODEL INNOVATION: EXPLORING THE IMPACT OF THE TEN TYPES OF INNOVATION FRAMEWORK - A CASE STUDY OF EKSPLORAKSI - Vigas Gibran, Muhammad
EksplorAksi, a workshop organizer based in Bandung, currently follows a traditional business model, which involves charging participants a fee to attend the workshop. However, the current business model lacks unique values that would encourage customers to consistently join the workshops, leading to unstable revenue. Failure to promptly identify an effective business model may result in future setbacks for EksplorAksi and decreased customer interest in workshop participation. Therefore, this research aims to identify the optimal business model innovation for EksplorAksi that aligns with customer expectations and contributes to business development. This research employs a qualitative approach and the data are collected through focus group discussions with EksplorAksi’s team members. The results highlight 34 successful business models, 15 unsuccessful business models, and 60 proposed business model innovations for the future. Ultimately, this research contributes to the workshop organizer field by identifying the optimal business model innovation for EksplorAksi, leading to increased revenue and workshop participation. The findings of EksplorAksi’s future business model innovations may not be applicable to other industries due to the specific context of its business. Future research should consider using different frameworks to further deepen business model analysis and broaden the scope to different industries.EksplorAksi, a workshop organizer based in Bandung, currently follows a traditional business model, which involves charging participants a fee to attend the workshop. However, the current business model lacks unique values that would encourage customers to consistently join the workshops, leading to unstable revenue. Failure to promptly identify an effective business model may result in future setbacks for EksplorAksi and decreased customer interest in workshop participation. Therefore, this research aims to identify the optimal business model innovation for EksplorAksi that aligns with customer expectations and contributes to business development. This research employs a qualitative approach and the data are collected through focus group discussions with EksplorAksi’s team members. The results highlight 34 successful business models, 15 unsuccessful business models, and 60 proposed business model innovations for the future. Ultimately, this research contributes to the workshop organizer field by identifying the optimal business model innovation for EksplorAksi, leading to increased revenue and workshop participation. The findings of EksplorAksi’s future business model innovations may not be applicable to other industries due to the specific context of its business. Future research should consider using different frameworks to further deepen business model analysis and broaden the scope to different industries.